A Short Asymmetric Synthesis of Octahydroindole Derivatives by Application of Catalytic C(sp3)–H Amination Reaction. Issue 1 (15th October 2013) - Mazurais, Marie; Lescot, Camille; Retailleau, Pascal; Dauban, Philippe
Abstract: The stereoselective synthesis of octahydroindole derivatives is reported according to 3–4‐step sequences. The strategy relies on our previously developed catalytic asymmetric C(sp 3 )–H amination reaction. Its application to cyclic enol triflates affords allylic amines in good yields and stereoselectivity. The C–H functionalization step, then, is followed by a Heck coupling reaction, a Mitsunobu reaction and a final intramolecular cycloaddition reaction thereby leading to the isolation of the expected heterocyclic compounds with an overall yield of up to 69 %. In addition, the chirality introduced in the intermolecular C(sp 3 )–H amination reaction allows controlling the configuration of the three other stereocenters created in the intramolecular cycloaddition reaction. A second sequence starts from benzocyclobutene and affords fused benzo‐octahydroindole derivatives over three steps. Abstract : The short stereoselective synthesis of octahydroindole derivatives is reported. Catalytic asymmetric C(sp 3 )–H amination reactions and stereoselective intramolecular cycloaddition reactions are the key steps of the strategy that affords an efficient versatile access to molecular diversity.